Pemeriksaan Angka Kapang Khamir Pada Pakaian Bekas Di Kota Mataram, Nusa Tenggara Barat, Indonesia - Anis Syakiratur Rizki; Lalu Srigede; Nurul Inayati (Otus Education: Jurnal Biologi dan Pendidikan Biologi, 2024)
Used clothing is an item that is worn by humans to cover their bodies but has been worn previously by other people and is a potential source of skin disease due to the growth of yeast or mold. This research aims to determine the number of yeast molds on used clothes sold in the city of Mataram. This research is descriptive exploratory in nature, while the used clothing in the study consisted of 11 samples which came from used clothing sold at Bertais market and Karang Sukun market. Based on the research results, it was found that the number of yeast mold colonies on used clothes from the Bertais market in sample 1 was 624,175 cfu/ml, in sample 2 colonies was 6,583,460 cfu/ml, in sample 3 colonies it was found to be 5,413,860 cfu/ml, in sample 4 it was obtained the number of colonies was 776,450 cfu/ml, and in sample 5 the number of colonies was 7,336,260 cfu/ml. Contamination of the number of yeast mold colonies found in used clothing at the Bertais market was less than the yeast mold contamination of clothing at the Karang Sukung market with the number of colonies in sample 1 being 27,244,700 cfu/ml, the colony in sample 2 was 4,688,888 cfu/ml, the number of colonies in sample 1 was 27,244,700 cfu/ml, the colony in sample 2 was 4,688,888 cfu/ml, sample 3 obtained as much as 5,989,880 cfu/ml, colony sample 4 obtained as much as 8,807,140 cfu/ml, colony sample 5 obtained as much as 1,634,333 cfu/ml, and colony sample 6 obtained as much as 5,545,640 cfu/ml.